2016
DOI: 10.7748/nop.2016.e811
|View full text |Cite
|
Sign up to set email alerts
|

Supporting people with dementia to eat

Abstract: The aim of this systematic review was to identify the best ways of supporting people with dementia to eat. Five electronic databases were searched, with a date range from January 2004 to July 2015. Following screening of the 233 studies identified, 22 were included in the final analysis. The study interventions focused on educational programmes, environmental or routine changes, and assistance with eating, with the strongest evidence shown in the more complex educational programmes for people with dementia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Twelve systematic reviews (Abdelhamid et al., 2016; Bunn et al., 2016; Fetherstonhaugh, Haesler, & Bauer, 2019; Hanson, Ersek, Gilliam, & Carey, 2011; Jackson, Currie, Graham, & Robb, 2011; Leah, 2016; Watson & Green, 2006; Wen, Jooyoung, & Thomas, 2014; Whear et al., 2014; Woodbridge et al., 2018; Yakimicki et al., 2019; Yi‐Hui et al., 2014) evaluated the effectiveness of environmental modifications, including lighting and contrast (7/12), home‐like environment (4/12), fish aquarium in dining area (6/12), music played during mealtimes (10/12), seated in the same location (1/12), and shared mealtime with others (3/12). According to the results, almost all of reviews showed that environmental modifications could be beneficial to increase food and drink intake.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve systematic reviews (Abdelhamid et al., 2016; Bunn et al., 2016; Fetherstonhaugh, Haesler, & Bauer, 2019; Hanson, Ersek, Gilliam, & Carey, 2011; Jackson, Currie, Graham, & Robb, 2011; Leah, 2016; Watson & Green, 2006; Wen, Jooyoung, & Thomas, 2014; Whear et al., 2014; Woodbridge et al., 2018; Yakimicki et al., 2019; Yi‐Hui et al., 2014) evaluated the effectiveness of environmental modifications, including lighting and contrast (7/12), home‐like environment (4/12), fish aquarium in dining area (6/12), music played during mealtimes (10/12), seated in the same location (1/12), and shared mealtime with others (3/12). According to the results, almost all of reviews showed that environmental modifications could be beneficial to increase food and drink intake.…”
Section: Resultsmentioning
confidence: 99%
“…Seven systematic reviews (Bunn et al., 2016; Fetherstonhaugh et al., 2019; Herke et al., 2018; Jackson et al., 2011; Leah, 2016; Sheppard, McArthur, & Hitzig, 2016; Wen et al., 2014) evaluated the effectiveness of education/training, including education and nutrition promotion programme for PWD (2/7), spaced retrieval activities training for PWD (5/7), Montessori‐based activities training for PWD (6/7), caregiver education (5/7), and feeding skills training programme for caregivers (4/7). Based on the result from Herke et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of interventions were considered in these reviews. Generally, interventions included use of oral supplementation/food fortification (12,15,16,18), eating assistance (12,13,(16)(17)(18)(19), environmental modification (13,14,16,18,19,21); staff education or training (16)(17)(18)(19); and food service/food delivery modification (14,16,20). Outcomes considered varied considerably including a range of psychological/psychosocial/behavioural measures, anthropometric measures such as weight and BMI, intake measures, functional measures such as eating ability/performance, satisfaction/perspective, and quality of life measures ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The broad, general nature of the recommendations was likely due to the relatively low quality of evidence, heterogeneity of findings, and the wide range of interventions and outcomes considered. Although few studies differentiated between types of staff, recommendations regarding staff in LTC settings included the need for increased training and education (12,14,(16)(17)(18)(19), and increased staff time/involvement (12,15). Two reviews made recommendations specific to care aides, calling for appropriate training/education (18,19) and one review recommended that care aides provide one-onone assistance to residents with dementia (19).…”
Section: Resultsmentioning
confidence: 99%